The accuracy of reporting of periprosthetic joint infection to the Australian Orthopaedic Association National Joint Replacement Registry. (2022) - Sinagra, Z. P.; Davis, J. S.; Lorimer, M.; Steiger, R. N. de; Graves, S. E.; Yates, P.
No abstract available